The Bhagavad Gita according to Gandhi : text and commentary translated from Gujarati - Gandhi, Mahatma (North Atlantic Books, 2009)
"Based upon talks given by Gandhi between February 24 and November 27, 1926 at the Satyagraha Ashram in Ahmedabad, India. During this time--a period when Gandhi had withdrawn from mass political activity--he devoted much of his time and energy to translating the Gita from Sanskrit into his native Gujarati. As a result, he met with his followers almost daily, after morning prayer sessions, to discuss the Gita's contents and meaning as it unfolded before him. This book is the transcription of those daily sessions. The Bhagavad Gita, also called The Song of the Lord, is a 700-line section of a much longer Sanskrit war epic, the Mahabharata. The Mahabharata is considered one of the greatest religious classics of Hinduism. The entire text of the Gita is a conversation between Krishna, an incarnation of the god Vishnu, and a general of one of the armies"--Provided by publisher.